2021
DOI: 10.3390/ijerph18052444
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Registered Randomized Controlled Trials for the Prevention of Obesity in Infancy

Abstract: Childhood overweight and obesity is a worldwide public health issue. Our objective was to describe planned, ongoing and completed randomized controlled trials (RCTs) designed for the prevention of obesity in early childhood. Two databases (World Health Organization International Clinical Trials Registry Platform, ClinicalTrials.gov) were searched to identify RCTs with the primary aim of preventing childhood obesity and at least one outcome related to child weight. Interventions needed to start in the first two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…A total of 14 RCTs were identified from the review (16) and formed the basis of forward searching (listed in Supplementary Table 1). A total of 1929 citations were obtained and 624 citations remained after de-duplication and 185 relevant papers were included after title and abstract screen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 14 RCTs were identified from the review (16) and formed the basis of forward searching (listed in Supplementary Table 1). A total of 1929 citations were obtained and 624 citations remained after de-duplication and 185 relevant papers were included after title and abstract screen.…”
Section: Resultsmentioning
confidence: 99%
“…We undertook a rapid review using all prescale trials included in a recent review with published outcomes undertaken by Mihrshahi et al (16) summarizing the effect of RCTs targeting nutrition, physical activity and obesity prevention in 0-2 year old children. To be included as a candidate for potential scale-up, the intervention was required to have reported a statistically significant effect on at least one weight, physical activity, nutrition, or parental feeding outcome.…”
Section: Methodsmentioning
confidence: 99%
“…First, the POI sleep intervention was brief, consisting in most cases of only two perinatal parent contacts (group education session in late pregnancy and home visit at 3 weeks post‐partum). While it has been suggested that interventions of long duration may be necessary to create sustained change, 28 these findings indicate that there is potential for sleep interventions to be brief, economical, 29 and effective 12,14 . Second, while the mean difference in BMI z ‐score at age 2 years may be considered small at −0.15 (95% CI −0.28 to −0.01), it agrees with a recent review of RCTs for the prevention of obesity in infancy, which found that differences in BMI z ‐scores reported ranged from −0.01 to −0.30 28 .…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested that interventions of long duration may be necessary to create sustained change, 28 these findings indicate that there is potential for sleep interventions to be brief, economical, 29 and effective 12,14 . Second, while the mean difference in BMI z ‐score at age 2 years may be considered small at −0.15 (95% CI −0.28 to −0.01), it agrees with a recent review of RCTs for the prevention of obesity in infancy, which found that differences in BMI z ‐scores reported ranged from −0.01 to −0.30 28 . It has been suggested that in early childhood obesity interventions, differences in mean BMI z ‐scores of as little as −0.12, if replicated widely, are enough to make important differences at a public health level 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation